Narrative mythology in the Indian version of the English language in the space of literary and philosophical tradition - D.O. Filippova (Язык и текст)
Context and relevance. In Russian and foreign linguistics, extremely great attention is paid to the issues of interaction and mutual influence of English variants in Internal, External and Expanding circles. Objective. To identify the features of narrative mythology in the Indian version of the English language in the space of literary and philosophical tradition. Hypothesis. The Indian version of English is considered through the prism of the cultural and historical tradition of India, Indian philosophy, the history of ancient Indian culture, literature, indigenous languages and is an important direction in literary studies and linguistics. Methods and materials. This study is devoted to the development of the provisions of contact variantology, the theory of differentiation of variants and their study in a comparative aspect. Results. This study shows that there is an undeniable connection between the mentality of the people, the author who belongs to this people, and the unique code reflected in the literary and philosophical space of the text. Conclusions. The influence of the literary and philosophical tradition in the mythology of the Indian English language is evident in many folklore and literary texts, which vividly reflects and demonstrates the relevance of this research.